The Western : four classic novels of the 1940s & 50s - Clak, Walter Van Tilburg, 1909-; Schaefer, Jack, 1907-1991; Le May, Alan, 1899-1964; Hall, Oakley M., 1920-2008 (Literary Classics of the United States, 2020)
"The golden age of the Western: four unforgettable novels of honor, adventure, and violence set against the magnificent landscapes of the American West"- Resumé vydavatel
Keywords: kovbojové -- Spojené státy americké (západní oblast); cowboys -- Spojené státy americké (západní oblast); americké romány; antologie; American fiction; anthology